Effect of aerosolized nicotine on human bronchial epithelial cells is amplified after co-administration with cannabidiol (CBD): a pilot in vitro study - Noel J. Leigh; Maciej L. Goniewicz (BMC, 2020)
Abstract Background Population-based studies suggest increasing rates of concurrent use of vaping products that contain either nicotine or cannabinoids. The aim of this pilot study was to test in vitro the acute inhalation toxicity of vaporized flavored and unflavored nicotine solutions co-administered with cannabidiol (CBD). Methods Bronchial epithelial cells (H292) were exposed directly to aerosol generated from electronic cigarettes refilled with propylene glycol only, unflavored nicotine solutions in propylene glycol with and without CBD, as well as to solutions containing only CBD. Cells were also exposed to a commercially available flavored solution containing nicotine and CBD. The in vitro toxicological effects were assessed after exposure using the following methods: 1) a trypan blue exclusion assay (cell viability), 2) neutral red uptake assay (metabolic activity) and 3) ELISA (concentrations of inflammatory mediators). Results Unflavored solution containing only CBD was significantly more cytotoxic than unflavored solution containing only nicotine. Unflavored solution containing both CBD and nicotine was significantly more cytotoxic than unflavored solutions with only nicotine. Levels of released cytokines were significantly higher when cells were co-exposed to nicotine and CBD as compared to cells exposed to only nicotine or only CBD. Overall, flavored products showed increased toxicity as compared to unflavored solutions. Conclusions This pilot in vitro study suggests independent and additive toxic effects of vaporized nicotine and CBD. Observed toxic effects are accentuated by flavorings. Future studies are needed to determine the potential long-term health consequences of concurrent use of vaporized nicotine and cannabis products.